Sistem Informasi Retribusi Terminal Berbasis Website - Bantun, Suharsono; Sari, Jayanti Yusmah; S. Sagala, La Ode Hasnuddin; Hardianti, Hardianti; Selviani, Selviani (INFORMAL: Informatics Journal, 2022)
Retribution information system is very important and indispensable in a terminal. At the Sabilambo Kolaka Terminal, especially in recapitulating retribution income data, they still use recording in the ledger, this makes it difficult for terminal officers to make a report so that the process for reporting terminal retribution income data to the Transportation Office in its implementation is still not optimal and over time there are losses and losses. data collection in the form of sheets of paper. Based on these problems, the researchers conducted a study with the title "Case Study Terminal Retribution Information System: Sabilambo Terminal". The information system is made using HTML, CSS, Javascript and the PHP programming language and MySQL as the database and data management process. The results of this study can be concluded that the system created works well and meets the requirements of the Sabilambo terminal. This can be seen from the survey results obtained from the questionnaire (93.53), indicating a value. A (very good).